1996
DOI: 10.1046/j.1471-4159.1996.67020805.x
|View full text |Cite
|
Sign up to set email alerts
|

Annexins in the Human Neuroblastoma SH‐SY5Y: Demonstration of Relocation of Annexins II and V to Membranes in Response to Elevation of Intracellular Calcium by Membrane Depolarisation and by the Calcium Ionophore A23187

Abstract: The human neuroblastoma SH-SY5Y was found to express annexins I, II, IV, V, and VI by western blot analysis. Calcium-dependent membrane-binding proteins were isolated from SH-SY5Y and analysed by 2-dimensional gel electrophoresis. Proteins with Mr and p1 values similar to those of annexins I, II, Ill, IV, V, and VI were observed. The identity of annexins II and V was confirmed by western blotting. The membrane association of annexins II and V was studied in cells that had been stimulated to release noradrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…A similar punctate pattern has been observed by using immunocytochemistry to determine the localization of synaptobrevin and synaptophysin in PCI 2 cells (Chilote et al, 1995); synaptotagmin, rab3a, and synaptophysin in cultured hippocampal neurons (Matteoli et al, 1991(Matteoli et al, , 1992; NPY in the neuroblastoma NG1O8-l5 (Fried et al, 1995); and secretogranin 11 in SH-SY5Y (Giudici et al, 1992). The immunocytochemical staining pattern observed in this study is very different from the diffuse, uniform staining observed in our previous work on the distribution of annexins II and V in SH-SYSY (Blanchard et al, 1996). Annexin 11 is located at the plasma membrane and annexin V is a soluble protein distributed between the cytosol and the nucleus.…”
Section: Immunocytochemical Evidence For Vesicles In Sh-sy5ycontrasting
confidence: 99%
“…A similar punctate pattern has been observed by using immunocytochemistry to determine the localization of synaptobrevin and synaptophysin in PCI 2 cells (Chilote et al, 1995); synaptotagmin, rab3a, and synaptophysin in cultured hippocampal neurons (Matteoli et al, 1991(Matteoli et al, , 1992; NPY in the neuroblastoma NG1O8-l5 (Fried et al, 1995); and secretogranin 11 in SH-SY5Y (Giudici et al, 1992). The immunocytochemical staining pattern observed in this study is very different from the diffuse, uniform staining observed in our previous work on the distribution of annexins II and V in SH-SYSY (Blanchard et al, 1996). Annexin 11 is located at the plasma membrane and annexin V is a soluble protein distributed between the cytosol and the nucleus.…”
Section: Immunocytochemical Evidence For Vesicles In Sh-sy5ycontrasting
confidence: 99%
“…Most members of the annexin family, including AnxA2, are recruited to cellular membranes in response to several stimuli that induce intracellular Ca 2ϩ mobilization (20). Interaction of AnxA2 at the N terminus with p11/S100A10 or by phosphorylation has been proposed to play a regulatory role in the Ca 2ϩ -dependent association to the cell membranes (21).…”
Section: Glutamate-induced Elevation In Intracellular Camentioning
confidence: 99%
“…It should be noted that compounds having the same scaffold were also reported as small molecule blockers of the interaction between S100A10 and annexin A2 [34]. Because both annexin A2 and FPR1 are involved in pathogenesis of tumor growth and invasion of neuroblastoma, glioma, and hepatocellular carcinoma [3537], development of FPR1 antagonists based on the 4-aroyl-3-hydroxy-5-phenyl-1 H -pyrrol-2(5 H )-one scaffold could lead to promising dual functional agents for the treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%